Evolution of internal regulations of public cultural institutions in relation to the organizer’s strategic documents - Smolny, Katarzyna (Ekonomia i Prawo. Economics and Law, 2026)
Motivation: previous research on the external and internal conditions of the functioning of public cultural institutions inspired the analysis of conditions resulting from the organizers’ strategic documents. Aim: Aim of this study is to answer the following questions: whether, do the organizer’s strategic regulations influence the internal organization of public theaters in Poland? Can these regulations influence the creation of formal conditions for co-management? Results: The lack of clear procedural and subjective requirements influences the dependence of public cultural institutions’ performance on individual, internal organizational solutions, suggesting the need for statutory unification of these processes and the issuance of implementing regulations. The current legal framework results in significant regulatory divergence across the country. Organizers, acting independently but in an uncoordinated manner, are crearors the management of public cultural institutions. The lack of uniform strategic documents causes discrepancies in management models.